Relations between Math Achievement, Math Anxiety, and the Quality of Parent-Child Interactions While Solving Math Problems - Michela DiStefano; Fraulein Retanal; Jean-François Bureau; Thomas E. Hunt; Anne Lafay; Helena P. Osana; Sheri-Lynn Skwarchuk; Philip Trepiak; Chang Xu; Jo-Anne LeFevre; Erin A. Maloney (MDPI AG, 2023)
In the current study, we used a multi-method approach to understand the quality of math homework-helping interactions between parents and their children and how parents' and children's own math achievement and math anxiety relate to the quality of the interaction. Forty Canadian parents and their children (ages 10-12 years; grades 5 to 7) completed self-report measures of math and general anxiety. Parents and children completed standardized assessments of math achievement and were then recorded as they engaged in a simulated math homework interaction. Coders assessed parent-child interaction quality during the interaction. Parent-child dyads generally performed well on the simulated math homework task. Nevertheless, task performance was correlated with the quality of the interaction, with high-quality interactions associated with high accuracy on the math task. Furthermore, the variability in the quality of the interaction was associated with parents' and children's math achievement and with the math anxiety of the children, but not the parents. Identifying the elements that influence parent-child interactions in math-related situations is essential to developing effective interventions to scaffold children's math learning and attitudes.